Training-induced annual changes in red blood cell profile in highly-trained endurance and speed-power athletes...This work was funded by the Polish Ministry of Science and Higher Education from financial resources of the National Science Centre within the OPUS 5 program (grant number 2013/09/B/NZ7/02556). - CIEKOT-SOLTYSIAK, Monika; KUSY, Krzysztof; PODGÓRSKI, Tomasz; ZIELIŃSKI, Jacek (Journal of Sports Medicine & Physical Fitness, 2018)
BACKGROUND: An extensive body of literature exists on the effects of training on hematological parameters, but the previous studies have not reported how hematological parameters respond to changes in training loads within consecutive phases of the training cycle in highly-trained athletes in extremely different sport disciplines. The aim of this study was to identify changes in red blood cell (RBC) profile in response to training loads in consecutive phases of the annual training cycle in highly-trained sprinters (8 men, aged 24±3 years) and triathletes (6 men, aged 24±4 years) who competed at the national and international level. METHODS: Maximal oxygen uptake (V02max) RBC, hemoglobin (Hb), hematocrit (Ht), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and RBC distribution width (RDW) were determined in four characteristic training phases (transition, general subphase of the preparation phase, specific subphase of the preparation phase and competition phase). RESULTS: Our main findings are drat: 1) Hb, MCH and MCHC in triathletes and MCV in both triathletes and sprinters changed significantly over the annual training cycle; 2) triathletes had significantly higher values than sprinters only in case of MCH and MCHC after the transition and general preparation phases but not after the competition phase when MCH and MCHC were higher in sprinters; and 3) in triathletes, Hb, MCH and MCHC substantially decreased after the competition phase, which was not observed in sprinters. The athletes maintained normal ranges of all hematological parameters in four characteristic training phases. CONCLUSIONS: Although highly-trained sprinters and triathletes do not significantly differ in their levels of most hematological parameters, these groups are characterized by different patterns of changes during the annual training cycle. Our results suggest that when interpreting the values of hematological parameters in speed-power and endurance athletes, a specific phase of the annual training cycle should be taken into account.